Analysis of the Factors Influencing the Disclosure Quality of Sustainability Reports in Companies in Indonesia - Ali, Fifitri (Jurnal Mutiara Ilmu Akuntansi, 2023)
Sustainability reports are useful for disclosing the company's performance on economic, environmental and social aspects, as well as the company's efforts to become a company that is accountable to all company stakeholders in general and also to society in a broad context. The report describes all business activities carried out for reporting responsibility to parties who need information as a form of transparency on activities carried out by the company. This study aims to find out the quality of disclosure of sustainability reports on companies in Indonesia and the effect of company size on the quality of disclosure of sustainability reports. This research uses companies listed on the Indonesia Stock Exchange in 2021. The samples to be taken are 38 companies that meet the predetermined criteria. To measure the level of quality of disclosure of sustainability reports, researchers use the disclosure index method, using a scale of 0 to 3 of the standard disclosures set by the Global Reporting Initiative (GRI). The results of the study show that the level of quality of sustainability report disclosure is at the lowest level of assessment with the Bronze predicate in the disclosure of sustainability reports